Nutritional Value of Fermented Rice Bran for Broiler Chickens: Apparent Metabolizable Energy and Growth Performance - Nalle , Catootjie L.; Yowi, Marlin R.K. (International Journal of Poultry Science, 2019)
Background and Objectives: The inclusion level of rice bran in broiler diets is limited due to its anti-nutritional factors such as phytic acid and fibre. Thus, this study was designed to evaluate the effect of solid fermentation of rice bran on the nutrient composition and feeding value for broilers. Materials and Methods: Experiment I: The apparent metabolisable energy of fermented rice bran (FRB), unfermented rice bran (UFRB) and yellow corn (as a reference) was determined using 64 growing broilers (28-35day). The assay diets were developed by substituting yellow corn, FRB and UFRB at 500 and 250 g kg–1 (w/w), respectively, of the basal diet. All diets were offered ad libitum to four cages containing 4 birds per cage. Experiment II: The feeding value of fermented rice bran was investigated. The experiment was designed using completely randomized design with six treatments and four replicates (10 birds/cage). A total of 240 day-old broilers were randomly distributed to 24 experimental units. The assay diets (0-250 g kg–1 FRB) were offered ad libitum to broilers from 0-21day. Data were analysed using ANOVA. Results: In experiment I, the results showed that the AME/n values of FRB were found to be higher (p<0.05) than the AME/n values of UFRB but it was comparable (p>0.05) to the AME/n values of yellow corn. In the experiment II, the different inclusion level of FRB significantly (p<0.01) affected the body weight gain (BWG) and feed intake of broilers but it did not affect (p>0.05) feed per gain and mortality rate. The BWG of birds fed on diets containing 0-150 g kg–1 of the FRB was lower (p<0.05) than those fed on diets containing 100-250 g kg–1 of the FRB. Birds given diets containing 100-250 g kg–1 FRB had similar (p>0.05) BWG. Conclusion: FRB is a good source of energy and amino acids and can be included up to 250 g kg–1 in broiler ration without a negative impact on the performance.